Stomach Content Analysis of Red Snakehead Fish (Channa micropeltes Cuvier, 1831) in Lubuk Siam Lake, Siak Hulu Sub-Regency, Kampar Regency, Riau Province - Fitri Natasha; Deni Efizon; Eddiwan Eddiwan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT Red snakehead (Channa micropeltes) fish is one of freshwater fish species that inhabit the Lubuk Siam Lake. Information on the type of red snakehead fish food, however, is limited. A research aims to understand the stomach content of red snakehead fish has been conducted in January to March 2018. The fish was sampled three times, once/month. There were 54 fishes captured. Stomach contents were analyzed using in a gravimetric method and data obtained were used for calculating the Preponderance Index (PI). Results shown that the food of red snakehead fish consists of fish, crustaceans and plant material. The main food of red snakehead fish is fish (PI 95%), complementary food is shrimp (PI 4%) and plant as additional food (PI 1%). Based on the data obtained, red snakehead fish can be categorized as pure carnivore.Keywords: Carnivore, Preponderance Index, Gravimetric, Oxbow Lake